2016
DOI: 10.1097/md.0000000000004794
|View full text |Cite
|
Sign up to set email alerts
|

Association between genetic polymorphisms of MMP8 and the risk of steroid-induced osteonecrosis of the femoral head in the population of northern China

Abstract: Background:Steroid-induced osteonecrosis of the femoral head (ONFH) is the most common clinical nontraumatic ONFH. Once ONFH occurs, it seriously reduces patients’ quality of life. The matrix metalloproteinase/tissue inhibitor of metalloproteinase (MMP/TIMP) system was found to play a significant role in the development of ONFH. The aim of this study was to identify the associations between 7 genes selected from the MMP/TIMP system and steroid-induced ONFH.Methods:We genotyped 34 single-nucleotide polymorphism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 37 publications
0
40
0
Order By: Relevance
“…The Association Research Circulation Osseous (ARCO) classification system was used for radiographic evaluation (Table ) (Gardeniers, Gosling‐Gardeniers, & Rijnen, ; Gardeniers,). Steroid‐induced ONFH was defined by a history of a mean daily dose ≥16.6 mg or a highest daily dose of 80 mg of prednisolone equivalent within 1 year prior to the development of symptoms or radiological diagnosis in asymptomatic cases (Du et al, ; Eichelbaum, Fromm, & Schwab, ; Zhao, Li, & Guo, ). Participants were excluded on the basis of having traumatic ONFH, dislocation of the hip joint, with histories of drinking more than 400 ml ethanol per week, significant familial hereditary disease, or other hip diseases.…”
Section: Methodsmentioning
confidence: 99%
“…The Association Research Circulation Osseous (ARCO) classification system was used for radiographic evaluation (Table ) (Gardeniers, Gosling‐Gardeniers, & Rijnen, ; Gardeniers,). Steroid‐induced ONFH was defined by a history of a mean daily dose ≥16.6 mg or a highest daily dose of 80 mg of prednisolone equivalent within 1 year prior to the development of symptoms or radiological diagnosis in asymptomatic cases (Du et al, ; Eichelbaum, Fromm, & Schwab, ; Zhao, Li, & Guo, ). Participants were excluded on the basis of having traumatic ONFH, dislocation of the hip joint, with histories of drinking more than 400 ml ethanol per week, significant familial hereditary disease, or other hip diseases.…”
Section: Methodsmentioning
confidence: 99%
“…Viable transplantation studies show that MMP‐9 may be involved in bone regeneration mediated by stem cells (Mosig et al., ). In our previous study, we have demonstrated that MMP‐8,MMP‐9 single‐nucleotide polymorphisms are related to steroid‐induced ONFH in Chinese population (Du, Jin, et al., ; Du, Lin, et al., ).…”
Section: Introductionmentioning
confidence: 96%
“…With the wide application of glucocorticoid in the treatment of rheumatic diseases, autoimmune diseases, hematopoietic system diseases, and other diseases, steroid-induced osteonecrosis of the femoral head (steroid-induced ONFH) has become the most common non-traumatic osteonecrosis of the femoral head (ONFH) type in clinical practice [1,2]. Epidemiological studies in East Asia have shown that 47.4% of all cases diagnosed as non-traumatic ONFH arose as a direct result of steroids [3].…”
Section: Introductionmentioning
confidence: 99%